Kerangka Decision Support System Berbasis Aturan untuk Evaluasi Izin Mendirikan Bangunan di Kawasan Rawan Longsor dan Banjir Kasus Kabupaten Bogor - Dyah Sulistyowati Rahayu; Nenden Nuraini; Zidan Wali Arubusman; Chaerul Cahyadi (Yayasan Petra Harapan Bangsa, 2025)
Bogor Regency is highly vulnerable to landslides and floods due to its geomorphology, intense rainfall, and increasing development pressure. The demand for building permits (IMB/PBG) in this area poses a policy dilemma because residential development in vulnerable zones can increase the risk of losses. This study aims to develop a decision-support system (DSS) framework to assist the government in evaluating the feasibility of residential building permits in an objective, transparent, and risk-based manner. The research method uses a literature review approach to examine relevant feasibility criteria, including geotechnical and hydrological factors, as well as regulatory aspects. The synthesis results in a rule-based DSS framework with three decision outputs: Go (feasible), Special Mitigation (conditional permit with technical requirements such as stilt houses, pile foundations, or slope drainage), and No-Go (not feasible). The contribution of this research is to provide a conceptual DSS model that can be integrated with the Building Licensing System (SIMBG) to support policy consistency, strengthen disaster mitigation, and improve spatial planning accountability in Bogor Regency.